Topologies on Superspaces of TVS-Cone Metric Spaces - Xun Ge; Shou Lin (The Scientific World Journal)
This paper investigates superspaces 𝒫0(X) and 𝒦0(X) of a tvs-cone metric space (X,d), where 𝒫0(X) and 𝒦0(X) are the space consisting of nonempty subsets of X and the space consisting of nonempty compact subsets of X, respectively. The purpose of this paper is to establish some relationships between the lower topology and the lower tvs-cone hemimetric topology (resp., the upper topology and the upper tvs-cone hemimetric topology to the Vietoris topology and the Hausdorff tvs-cone hemimetric topology) on 𝒫0(X) and 𝒦0(X), which makes it possible to generalize some results of superspaces from metric spaces to tvs-cone metric spaces.